1994
DOI: 10.1056/nejm199401063300103
|View full text |Cite
|
Sign up to set email alerts
|

Declining Incidence of Nephropathy in Insulin-Dependent Diabetes Mellitus

Abstract: During the past decade the cumulative incidence of diabetic nephropathy, as manifested by persistent albuminuria, among patients who have had diabetes for 25 years has decreased substantially, probably as a result of improved glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
235
2
7

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(253 citation statements)
references
References 21 publications
9
235
2
7
Order By: Relevance
“…In the Linköping Diabetes Complications Study we observed a marked decline in the incidence of diabetic nephropathy, from 28% to 9% after 20 years of diabetes, in an unselected population of Type 1 diabetes diagnosed between 1961 and 1980 [8]. However, we could not find a significant decrease of severe, lasertreated retinopathy [9].…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…In the Linköping Diabetes Complications Study we observed a marked decline in the incidence of diabetic nephropathy, from 28% to 9% after 20 years of diabetes, in an unselected population of Type 1 diabetes diagnosed between 1961 and 1980 [8]. However, we could not find a significant decrease of severe, lasertreated retinopathy [9].…”
contrasting
confidence: 63%
“…When the patients were divided into 5-year cohorts according to the time of diagnosis, there was a declining trend in the cumulative proportion of severe retinopathy after 25 to 30 years of diabetes. Furthermore the previously reported marked decrease in the cumulative proportion of diabetic nephropathy persisted [8]. We defined severe retinopathy as laser-treated retinopathy, because it is more definite than just proliferative retinopathy or macular oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between glycaemic control at baseline and percentage of subjects progressing to macroalbuminuria at follow-up. *p<0.05 and **p<0.01 vs HbA 1 c ≤5.5% and according to older epidemiological studies [19,20], persistently microalbuminuric patients may be at relatively low risk of progressing to that condition. However, in a recent study [21], the rate of progression to macroalbuminuria in patients with diabetes duration in excess of 30 years was 4.5 per 100 person-years, supporting the notion that even Type 1 diabetic patients with long disease duration may show a significant rate of progression to overt nephropathy.…”
Section: Discussionmentioning
confidence: 97%
“…As Kussman et al remarked in 1976, "once the clinical signs of nephropathy have become manifest, the natural course is inexorably progressive to death" [9]. There was, therefore, considerable interest in a study from Sweden that, in 1994, reported a dramatic decline in the incidence of diabetic nephropathy: the 20-year cumulative incidence fell from 28% in patients with onset of type 1 diabetes from 1961-1965 to only 5.8% in patients with onset of diabetes from 1971-1975 [11]. Furthermore, not one patient diagnosed between 1976 and 1980 developed persistent proteinuria [11].…”
Section: The Changing Course Of Diabetic Kidney Diseasementioning
confidence: 99%
“…There was, therefore, considerable interest in a study from Sweden that, in 1994, reported a dramatic decline in the incidence of diabetic nephropathy: the 20-year cumulative incidence fell from 28% in patients with onset of type 1 diabetes from 1961-1965 to only 5.8% in patients with onset of diabetes from 1971-1975 [11]. Furthermore, not one patient diagnosed between 1976 and 1980 developed persistent proteinuria [11]. These excellent results were probably due to the work of a dedicated team that achieved glycaemic control equivalent to that seen in an intensively treated group in the DCCT study [12].…”
Section: The Changing Course Of Diabetic Kidney Diseasementioning
confidence: 99%